Currency identification assistant for visually impaired / Nabill Hidzir Pauzi and Shahrul Azam Abdullah - Hidzir Pauzi, Nabill; Abdullah, Shahrul Azam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
As a rapidly developing country, Malaysians in general enjoy technologically advanced services and facilities. However, disabled people such as visually impaired group may face barriers to conduct basic activities because. One of a very difficult task for a person with visual impairment is to identify and differentiate Malaysian Ringgit notes from each other. Therefore, a device is needed to accommodate the need of this group. This paper will focus on development of a device to address the abovementioned issue. The main objective of the project was to build a prototype handheld device that will be able to differentiate Malaysian notes and recognize it accurately. The design is developed using a computer-aided design software; CATIA V5R20 and the conceptual design were visualized using three-dimensional printer. The devices are designed to be at low cost to fabricate allowing them can be owned by the visually impaired people without any hassle.